Nature Mentors: a program to encourage outdoor activity and nature engagement among urban youth and families. Issue 1 (2nd January 2021) - Hackett, Kelly A.; Ziegler, Michael C.; Olson, Jared A.; Bizub, Jessica; Stolley, Melinda; Szabo, Aniko; Heller, Elizabeth; Beyer, Kirsten M. M.
ABSTRACT: Significant declines in outdoor activity and engagement with the natural environment are growing concerns with negative impacts on well-being. We pilot-tested an intervention encouraging outdoor activity among adult mentor and child mentee pairs and families, in partnership with Milwaukee's Urban Ecology Center. The study used a mixed methods approach, including pre and post-program surveys and in-depth interviews. Findings indicate the significance of environmental barriers to behavior change, especially in urban areas, as well as the potential utility of programs like Nature Mentors in producing shifts towards more time spent outdoors and in contact with nature.